2011
DOI: 10.1364/oe.19.00a851
|View full text |Cite
|
Sign up to set email alerts
|

On the interplay of waveguide modes and leaky modes in corrugated OLEDs

Abstract: Bragg gratings incorporated into organic light-emitting diodes (OLEDs) establish a coupling between waveguide modes and useful light (leaky modes). Here we demonstrate that the net coupling direction depends on the OLED stack design. We fabricated two different device structures with gold Bragg gratings. Angle resolved electroluminescence spectra were recorded. For the first device peaks of enhanced emission due to the Bragg grating are observed corresponding to a net energy transfer in direction of the leaky … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
28
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 27 publications
(29 citation statements)
references
References 25 publications
1
28
0
Order By: Relevance
“…2(c). These findings are in agreement with recent results in [24] where we discussed the complex interplay of scattering processes between waveguide modes, substrate modes and radiation modes. For certain geometries the losses due to enhanced incoupling of radiation modes into waveguide modes might overcompensate the enhanced outcoupling of waveguide modes into radiation modes.…”
Section: Measurement and Resultssupporting
confidence: 93%
“…2(c). These findings are in agreement with recent results in [24] where we discussed the complex interplay of scattering processes between waveguide modes, substrate modes and radiation modes. For certain geometries the losses due to enhanced incoupling of radiation modes into waveguide modes might overcompensate the enhanced outcoupling of waveguide modes into radiation modes.…”
Section: Measurement and Resultssupporting
confidence: 93%
“…Hence, the emission from Device C cannot be understood simply as the emission of a planar microcavity with superposed Bragg scattering. The weak perturbation approach previously discussed by Hauss et al [34] and Fuchs et al [28] does not suffice to describe these experimental data, despite the fact that the previously mentioned thickness criterion h C /d opt = 0.33 < 1 holds. This thickness criterion was originally derived for weak optical microcavities of dielectric media excluding metals within the optical microcavity [33].…”
Section: Mode Analysis Of Top-emitting Oleds On Periodically Corrugatmentioning
confidence: 89%
“…Hauss et al [34] observed a reduction of emission in a corrugated bottom-emitting OLED due to a more prominent transfer of light intensity from the air cone into wave-guided modes in comparison to the reverse scattering of guided modes into the air cone. However, their approach cannot account for the absence of the fundamental cavity mode in our corrugated microcavity top-emitting OLEDs nor for the observed bending of the dispersion relations.…”
Section: Mode Analysis Of Top-emitting Oleds On Periodically Corrugatmentioning
confidence: 99%
“…The broad background is due to the light which was directly emitted from the OLED with wavevectors within the light escape cone and thus not affected by the photonic microstructures. Currently the most common method to model the spatial emission pattern of a microstructured OLED is simply to analyse the photonic dispersion of a grating by the Bragg condition [14][15][16][17]. This calculates the out-coupling elevation and azimuthal angles of trapped modes, but does not provide information about the relative power distribution of the far field emission.…”
Section: Introductionmentioning
confidence: 99%